2001
DOI: 10.1046/j.1365-2958.2001.02291.x
|View full text |Cite
|
Sign up to set email alerts
|

The cold‐shock stress response in Mycobacterium smegmatis induces the expression of a histone‐like protein

Abstract: SummaryThe response of Mycobacterium smegmatis to a cold shock was investigated by monitoring changes in both growth and cellular protein composition of the organism. The nature of the cellular response was influenced by the magnitude of the temperature reduction, with the shock from 378C to 108C having the most widespread effect on growth, metabolism and protein composition. This 278C temperature reduction was associated with a lag period of 21± 24 h before increases were seen in all the measured cellular act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 55 publications
5
53
0
Order By: Relevance
“…Several of these regulators have been characterized; some of them respond to environmental stresses such as cold shock (60), heat shock (41, 63), hypoxia (18,51,59), iron starvation (56), surface stress (41), and oxidative stress (42, 55), while others respond to still unknown environmental conditions (28,52,72). The resulting picture is still incomplete, but it suggests very complex regulatory systems with overlapping functions and redundancies.…”
mentioning
confidence: 99%
“…Several of these regulators have been characterized; some of them respond to environmental stresses such as cold shock (60), heat shock (41, 63), hypoxia (18,51,59), iron starvation (56), surface stress (41), and oxidative stress (42, 55), while others respond to still unknown environmental conditions (28,52,72). The resulting picture is still incomplete, but it suggests very complex regulatory systems with overlapping functions and redundancies.…”
mentioning
confidence: 99%
“…Hlp could also promote DNA end joining in the presence of DNA ligase and could repress transcription by T7 RNA polymerase (38). The low abundance and the fact that mutants lacking Hlp grew normally and were not affected in survival of cold shock or anaerobiosis show that additional proteins must be involved in organizing the chromatin structure in mycobacteria, e.g., homologs of IHF, H-NS and Dps, and the newly described DNA-bridging protein Lsr2 (10,31,49). Hlp was instead suggested to be involved in repair or recombination processes, like nonhomologous end joining, and in regulating gene activity in response to stressful conditions (38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although in B. subtilis none of these proteins has been examined with respect to a function during the cold shock response, it was shown that in E. coli gyrase and HU proteins (HBsu homologues) function in concert (Mizushima et al 1997). In fact, HU proteins are essential during cold shock adaptation of E. coli (Wada et al 1988) and in Mycobacterium smegmatis a histone-like protein is one of the major cold-induced proteins (Shires & Steyn 2001). Since SspF is currently the only SASP to which no specific function has been assigned during sporulation (Loshon et al 1997), it might be interesting to investigate whether it is of relevance to the cold shock response-especially in conjunction with HBsu which was shown to modulate the effects of SASPs, at least in vitro (Ross & Setlow 2000).…”
Section: Nucleoid Structure and Transcriptionmentioning
confidence: 99%